2021
DOI: 10.1093/jat/bkab018
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 5- and 6-APB in Blood, Other Body Fluids, Hair and Various Tissues by HPLC--MS-MS

Abstract: 5-(2-aminopropyl)benzofuran (5-APB) and 6-(2-aminopropyl)benzofuran (6-APB) are benzofuran analogues of amphetamine and belong to the category of new psychoactive substances (NPS). Despite already published fatal 5- and 6-APB intoxication - in most cases, a combination of both substances - no sensitive method for the simultaneous detection and quantification of these new psychoactive compounds in human blood samples has yet been developed. Therefore, an easy and fast sample preparation-, as well as specific hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… Hofmann et al (2021) reported a fatal case in Germany involving two stereoisomers (5- and 6-(2-aminopropyl)benzofuran), which are substituted benzofuran phenethylamines. Concentrations ranged from 300 to 2,400 ng/ml in blood and from 2,100 ng/ml in bile to 65,000 ng/ml in stomach content.…”
Section: Fatal Cases Involving New Psychoactive Substance Intakementioning
confidence: 99%
“… Hofmann et al (2021) reported a fatal case in Germany involving two stereoisomers (5- and 6-(2-aminopropyl)benzofuran), which are substituted benzofuran phenethylamines. Concentrations ranged from 300 to 2,400 ng/ml in blood and from 2,100 ng/ml in bile to 65,000 ng/ml in stomach content.…”
Section: Fatal Cases Involving New Psychoactive Substance Intakementioning
confidence: 99%
“…These benzofurans have a similar chemical structure to MDMA (ecstasy) and MDA (Figure 1), two well-known illicit drugs [3,4]. Due to their popularity among users, reports of serious intoxication, including some fatalities, have emerged (there have been several fatal cases of the simultaneous consumption of 5-APB and 6-APB) [5][6][7][8][9][10]. Similar to MDMA and MDA, 5-APB and 6-APB are known for their entactogenic effects, which is a primary reason for their popularity among users.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of information is compounded by the difficulty of developing reliable detection methods. However, a recent breakthrough has been made in this area with the development of a highly sensitive method for the simultaneous detection and quantification of both 5-APB and 6-APB in human blood samples [10]. In vitro studies in primary rat hepatocytes of the two benzofurans, 6-APB and 5-APB, showed that 5-APB Molbank 2023, 2023, M1629 2 of 7 displayed higher hepatotoxicity in these cellular models than its 6-isomer [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations